Invasive Pest Species: Impacts On Agricultural Production, Natural Resources, And The Environment - Huber, Don M.; Hugh-Jones, Martin E.; Rust, Michael K.; Sheffield, Steven R.; Simberloff, Daniel; Taylor, C. Robert (Council for Agricultural Science and Technology (CAST), 2002)
This CAST issue paper provides policymakers and others with a nine-step guide to curtail the impact of non-native pests, including diseases, insects, and animals. These pests are the source of an estimated $137 billion annual economic burden to the United States and are the second leading cause of species endangerment. In addition, bioterrorism introduces another unknown risk factor into the already unstable mix of detrimental exotic species.
Keywords: Invasive Pest Species; Natural Resources; Environment